Model Kebijakan Penetapan Institusi Masjid sebagai Shelter dalam Sistem Logistik Bencana di Kota Padang - Winny Zilkhalida Hadi; Rika Ampuh Hadiguna (Jurnal Optimasi Sistem Industri, 2015)
The west coast of Sumatera island is one of potential areas of the earthquake and tsunami that requires high vigilance and preparedness seriously. One is the well-prepared-disaster logistics system. World Health Organization (WHO) has been divided into 10 categories of logistics, including the temporary shelter. The purpose of this study is to study attributes that should be required for the mosque as a shelter for victims of the earthquake and tsunami in Padang and provide recommendations to the government of Padang to prepare the mosque as a shelter. Formulation of mosque attributes as a shelter eligibility has been obtained through literature review and interviews. Attributes have been formulated in the form of questionnaires that filled out by prospective refugees of the earthquake and tsunami in Padang . Result of questionnaire has been used to build the House of Quality (HOQ). Furthermore, a SWOT analysis has been conducted to formulate a strategy for local government in an effort to empower mosques as shelters in Padang.This research has resulted 14 attributes of feasibility mosque as a shelter. Attributes divided into seven categories. Strategies that result based SWOT analysis have nine formulations that consists of two SO strategies, four WO strategies, two ST strategies, and one WT strategies. Implementation of this strategies required responsibility and cooperation between government, community, NGO, and leaders.